(3CYeGd fgGjI GdSfI hab GdfXGe GdeMGSHj GdeGdj (BSCFs - (3MSfGA(B, (3eTQjs ((3GdLRGFQ(B:s (3OGQ GdHGMK ddfTQ hGdETgGQ(B,s, 2022)
(3GdGWGQ GdeaGgjej dCYeGd fgGjI GdSfI,eDhfGJ GdCNWGQ hGdCYHGA, LQO GdJKHjJGJ, GdJfGRdGJ Yf GdJKHjJGJ hGdCUhd GdeGdjI, LQO GdeNRhf, LQO MSGHGJ GdYedGA, LQO MSGHGJ GdehQOjf, JShjI MSGHGJ GdCYHGA, JShjI MSGHGJ GdfJGFL, EYOGO ejRGf GdeQGLYI hGdcTha GdeGdjI(B.s
(3eQGLY U(B.141s
Keywords: (3GdeMGSHI GdJMdjdjIs; (3GdfXGe GdeGdjs